Reconciling COVID-19 pandemic budget deficits through furloughs and salary reductions. Issue 2 (27th December 2021) - Bumpus, Minnette A.
Abstract : Theoretical basis: The primary topics, in this case, align well with social processes relative to communication and decision-making, and with individual processes relative to fairness in the workplace. Research methodology: The case was developed from secondary sources. The secondary sources included news reports, and university sources (i.e. e-mails, announcements, reports, town hall meetings). This descriptive case has been classroom tested in an undergraduate organizational behavior course. Case overview/synopsis: On September 10, 2020, the president of Bowie State University, Dr Aminta H. Breaux, announced that the university needed to "take a number of steps, including a temporary salary reduction plan, to close the FY21 funding gap and position the university for continued budget challenges" (Exhibit 1 ) triggered by the economic impact of COVID-19 on the state of Maryland. Some of the faculty members' reactions to this announcement included shock and disappointment. Reflecting on what led to the state appropriation reductions, why would faculty members be shocked by President Breaux's announcement of temporary salary reductions? Did President Breaux make the right decision, and was it communicated appropriately? Complexity academic level: This descriptive case is most appropriate for undergraduate level organizational behavior courses.